Biomaterials delivery strategies to repair degenerated intervertebral discs by regulating the inflammatory microenvironment - Xia, Yuanliang; Wang, Hengyi; Yang, Ruohan; Hou, Yulin; Li, Yuehong; Zhu, Jianshu; Fu, Changfeng (Frontiers in Immunology, 2023)
Intervertebral disc degeneration (IVDD) is one of the main causes of lower back pain. Although IVDD cannot directly cause death, it can cause pain, psychological burdens, and economic burdens to patients. Current conservative treatments for IVDD can relieve pain but cannot reverse the disease. In patients with advanced IVDD, only the surgical removal of the degenerated disc can be performed. However, the surgical removal of IVDD can affect the stability of adjacent discs. Furthermore, the probability of the reherniation of the intervertebral disc (IVD) after surgery is as high as 21.2%. Strategies based on tissue engineering to deliver stem cells for the regeneration of nucleus paposus (NP) and annulus fibrosus (AF) have been extensively studied. The developed biomaterials not only locally withstand the pressure of the IVD, but also lay the foundation for the survival of stem cells. However, the structure of IVDs does not provide sufficient nutrients for delivered stem cells. The role of immune mechanisms in IVDD has recently become clear. In IVDD, the IVD that was originally in immune privilege prevents the attack of immune cells (mainly effector T cells and macrophages) and aggravates the disease. Immune regulatory and inflammatory factors released by effector T cells, macrophages and the IVD further aggravate IVDD. Reversing IVDD by regulating the inflammatory microenvironment is a potential approach for the treatment of the disease. However, the biological factors that modulate the inflammatory microenvironment are easily degraded in vivo. This makes it possible for different biomaterials to modulate the inflammatory microenvironment to repair IVDD. In this review, we have discussed the structures of IVDs and immune mechanisms underlying IVDD. We have described the immune mechanisms elicited by different biological factors including tumor necrosis factors, interleukins, transforming growth factors, hypoxia-inducible factors, and reactive oxygen species in IVDs. Finally, we have discussed the biomaterials used to modulate the inflammatory microenvironment to repair IVDD and their development.